PENGARUH FAKTOR HYGIENE DAN MOTIVATOR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. RIANTO PRIMA JAYA - Stevianus Stevianus (Jurnal Ilmiah Ekonomi Bisnis, 2015)
The company's main goal to achieve maximum profit, so that the company's goals can be achieved, then the company should have a high effectiveness. Companies and employees are two things that need each other. The success employees of self-actualization of potential and an opportunity to meet their needs. As for the company, success is a means towards the growth and development of the company. The company's success is determined in part by either the employee job satisfaction.The population of study was employees of PT. Rianto Prima Jaya, amounting to 90 employees. The sampling technique used in this study is the Proportional stratified random sampling by taking a sample of 90 people. According Sugiyono (2007: 75), this technique is used when the population has members or elements that are not homogeneous and stratified proportionally. Measurement of variables in this study will use a Likert scale. This data was obtained through HRD in the company. This data is in the form of number of employees, section or division. The interview is with a question and answer directly to the employees of the company and the respondent regarding the motivation, job satisfaction, and employee performance in an organization or company. The questionnaire is to provide a list of written questions to the respondent on motivational factors and hygiene factors and job satisfaction PT. Rianto Prima Jaya. Validity is an instrument that can be used to measure what should be measured. This test is done to approach product moment correlation between each of the items that measure a variable with a total score of the variables. Reliability test was conducted to determine the level of consistency of measurement results when the data measured twice or more the same symptoms.The results showed that the variables of Hygiene negative effect and no significant effect on Employee Satisfaction at PT. Rianto Prima Jaya,, while Motivator variables provide a significant and positive effect on employee job satisfaction. Correlation / relationship between hygiene and motivator factors with job satisfaction of employees of PT. Rianto Prima Jaya is high enough for (r = 0710) in which the adjusted R-square is equal to 0710 this means 71% of the variation in the dependent variable job satisfaction of employees at PT. Rianto Prima Jayayang can be explained by the independent variables of Hygiene and Motivatorsedangkan the balance of 0.290 or 29% is explained by other variables outside the existing variable. Keywords: hygiene, motivator, job satisfaction